ANALISIS FAKTOR-FAKTOR PREFERENSI KONSUMEN YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SAYURAN ORGANIK (STUDI KASUS : PELANGGAN SUPER INDO SEMARANG) - Fernanda Florencia Pramono; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2017)
As lifestyle changes, increased knowledge and income as well as public awareness of safer organic foods resulting increased demand especially for vegetables. Currently, many Indonesia’s modern retailers are marketing organic vegetables causing competition between organic vegetable companies becomes tighter. The company has an important role in attracting consumer preference to purchase organic vegetables by using consumer preference factors.The purpose of the research is to know what factors make up the consumer preference and its effect to the decision of purchasing organic vegetables.The research method is quantitative research with explanatory research type. Data analysis techniques used are validity test, reliability test, exploratory factor analysis, correlation coefficient, coefficient of determination, multiple linear regression analysis, F test, and t test.The result of the research shows consumer preference factors that influence purchase decision are physical product quality factor, pricing, and promotion. While the store’s safety and comfortable, the appropriateness of the price, the location of the store, the availability, and the price information has no effect on purchasing decisions of organic vegetables.This research suggests the companies to set organic vegetables marketing strategy based on consumer preferences, as well as a contribution of thought to enrich existing research in Indonesia.